2019
DOI: 10.1039/c9ra05722f
|View full text |Cite
|
Sign up to set email alerts
|

Changes in magnetic order through two consecutive dehydration steps of metal-phosphonate diamond chains

Abstract: M3II(hpdpH)2(H2O)6·4H2O (M = Co, Ni) experience identical two-step dehydration processes associated with drastic magnetic changes from paramagnet to antiferromagnet/metamagnetic to ferrimagnet for M = Co, and from antiferromagnet to antiferromagnet to ferrimagnet for M = Ni.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…CoU-190 shows the longest relaxation time, in accordance with the fact that the Co(II) ion in CoU-190 has a quasi-two-coordinate environment. Dehydration-induced magnetic changes were previously observed in cobalt systems, [61][62][63] but those related to single-ion magnetic behavior were rare. [64,65] It is interesting that the restacked nanosheets of CoU-ns show magnetic relaxation much faster than the pristine CoU.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…CoU-190 shows the longest relaxation time, in accordance with the fact that the Co(II) ion in CoU-190 has a quasi-two-coordinate environment. Dehydration-induced magnetic changes were previously observed in cobalt systems, [61][62][63] but those related to single-ion magnetic behavior were rare. [64,65] It is interesting that the restacked nanosheets of CoU-ns show magnetic relaxation much faster than the pristine CoU.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…[8][9][10][11] Among them, cobalt-based MOFs are of particular interest because cobalt ion can show multiple oxidation states, variable coordination numbers and tunable spin states that can be sensitive to environment changes. [12][13][14][15][16][17][18] For example, Dincă et al reported the reversible storage of elemental chlorine and bromine in a robust Co-azolate MOF which operated via redox mechanism. [19] Pardo and Cano et al found that single-ion magnet behavior of a 2D Co-MOF can be tuned by changing the guest aromatic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐organic frameworks (MOFs) with their structures and properties responsive to external stimuli, such as gas/guest, [1–3] pressure, [4] temperature [5] and light, [6,7] are very attractive owing to their potential applications in gas storage and separation, drug delivery, sensors, catalysis and molecular devices [8–11] . Among them, cobalt‐based MOFs are of particular interest because cobalt ion can show multiple oxidation states, variable coordination numbers and tunable spin states that can be sensitive to environment changes [12–18] . For example, Dincă et al.…”
Section: Introductionmentioning
confidence: 99%